Workshop Pemrograman Android menggunakan AppInventor untuk Tim Musyawarah Guru Mata Pelajaran (MGMP) TIK/Informatika Kota Padang - Rahmatika Pratama Santi; Husnil Kamil; Hasdi Putra; Haris Suryamen; Fajril Akbar; Jefril Rahmadhoni; Hafizah Hanim (Warta Pengabdian Andalas, 2023)
Android is a platform for smartphones that can be used anytime and anywhere. Smartphones can be felt in various aspects of human life, especially in education, as a medium of learning material between teachers and students. The development of Android-based applications needs special basic Android programming skills. The Informatics Subject Teacher Consultation of Padang (MGMP) is interested in developing a simple Android-based application but needs direction and guidance to learn Android programming. Therefore, a workshop was needed to develop an Android-based application using AppInventor for simple applications. The workshop provided more steps, essential knowledge, and new experience to be developed by MGMP Team to support duties as teachers.